تأثير التدخلات الخارجية على الأمن القومي الليبي (2011-2023): دراسة تحليلية (Journal of Academic Research, 2025)
Abstract:. This research provides an in-depth analysis of external interventions in Libya between 2011 and 2023, examining their various forms, their stated and unstated objectives, and their complex impact on Libyan national security. The report aims to provide a comprehensive understanding of the challenges facing Libyan sovereignty and internal stability as a result of these interventions. The analysis reveals that these interventions, often justified by humanitarian or security objectives, were driven by strategic and economic interests, eroding international law and exacerbating the Libyan crisis. The main findings indicate that direct and indirect military interventions, in addition to proxy conflicts, have led to the dismantling of Libyan military institutions, contributed to the proliferation of militias, organized crime, and human trafficking, and increased foreign influence along the borders. These interventions have also disrupted the political process, exacerbated internal divisions, deteriorated public services, and internationalized the Libyan crisis, leading to a significant erosion of national sovereignty. The report concludes that Libya's natural resources and geographical location, rather than being factors of strength, have become a driver of external interference, creating a vicious cycle of internal fragility and external exploitation. The report offers practical recommendations aimed at supporting the building of a unified and stable Libyan state by strengthening national institutions, achieving reconciliation, and unifying international efforts to uphold Libyan sovereignty .that Libya's natural resources and geographical location, rather than being factors of strength, have become a driver of external interference, creating a vicious cycle of internal fragility and external exploitation. The report offers practical recommendations aimed at supporting the building of a unified and stable Libyan state by strengthening national institutions, achieving reconciliation, and unifying international efforts to uphold Libyan sovereignty